Localization of the 47 kDa phosphoprotein involved in the respiratory-burst NADPH oxidase of phagocytic cells. - Heyworth, P G (1989)
A 47 kDa phosphoprotein is involved in the respiratory-burst oxidase of phagocytic cells. After stimulation of neutrophils with phorbol myristate acetate, this phosphoprotein was identified in both the cytosol and membranes. Peptide mapping of the two forms resulted in identical patterns of phosphopeptides. Dose-response curves for accumulation of phosphoprotein in the two sites were very similar, whereas the detection of the phosphoprotein in the cytosol preceded that in the membranes. The membrane-associated 47 kDa phosphoprotein was absent from the neutrophils of patients with X-chromosome-linked chronic granulomatous disease, which lack cytochrome b-245, and intermediate levels were detected in the membranes of their heterozygote carrier mothers. Activation of the neutrophil oxidase system appears to be dependent upon phosphorylation of the cytosolic 47 kDa protein and its association with cytochrome b-245 in the membranes. It is probably the cytosolic factor required for reconstitution of the active oxidase in cell-free systems.